UPAYA PENCEGAHAN DAN PENGENDALIAN COVID-19 DI PT. EXCELITAS TECHNOLOGIES BATAM - Isnaniyah Muharriani (Jurnal Kesehatan Masyarakat, 2022)
Coronavirus Disease-2019 is an infectious disease caused by SARS-CoV-2. This virus is very quickly transmitted between humans. The workplace is one of the places that involves many workers, resulting in the vulnerability of coronavirus transmission in the workplace. The purpose of this study is to determine measures to prevent and control COVID-19 at PT. Excelitas Technologies Batam City. This type of research is descriptive quantitative research. The research instrument used observation sheets, interview guides, and document study sheets. Data were analyzed by data reduction, presentation, and conclusion drawing. The result show that implementation of measures to prevent and control COVID-19 at PT. ETB are 70% compliant, 10% incompliant, and 20% unavailable. A suggestion for PT. ETB is to improve policies and facilities of controlling COIVD-19 in the workplace.